QMwebJS—An Open Source Software Tool to Visualize and Share Time-Evolving Three-Dimensional Wavefunctions - Edgar Figueiras; David N. Olivieri; Angel Paredes; Humberto Michinel (Mathematics, 2020)
Numerical simulation experiments are of great importance for research and education in Physics. They can be greatly aided by proper graphical representations, especially for spatio-temporal dynamics. In this contribution, we describe and provide a novel Javascript-based library and cloud microservice—QMwebJS—for the visualization of the temporal evolution of three-dimensional distributions. It is an easy to use, web-based library for creating, editing, and exporting 3D models based on the particle sampling method. Accessible from any standard browser, it does not require downloads or installations. Users can directly share their work with other students, teachers or researchers by keeping their models in the cloud and allowing for interactive viewing of the spatio-temporal solutions. This software tool was developed to support quantum mechanics teaching at an undergraduate level by plotting the spatial probability density distribution given by the wavefunction, but it can be useful in different contexts including the study of nonlinear waves.